The Costs and Benefits of Providing Open Space in Cities - Jan Rouwendal; J. Willemijn van der Straaten (Tinbergen Institute, 2008)
Although many researchers have investigated the value of open space in cities, few of them have compared them to the costs of providing this amenity. In this paper, we use the monocentric model of a city to derive a simple cost-benefit rule for the optimal provision of open space. The rule is essentially the Samuelson-condition for the optimal provision of a public good, with the price of land as the appropriate indicator for its cost. The condition is made operational by computing the willingness to pay for public and private space on the basis of empirical hedonic price functions for three Dutch cities. The conclusions with respect to the optimal provision of open space differ between the three cities. Further investigation reveals that willingness to pay for parks and public gardens increases with income, although not as fast as that for private residential space.
Keywords: R52; H41; D61; 330; spatial planning; provision of public goods; cost-benefit analysis; Raumordnungsplan; Kosten-Nutzen-Analyse; Öffentliche Güter; Willingness to pay; Niederlande